Strategy for the Implementation of the Policy for Installing Transaction Recording Equipment as Monitoring Regional Taxes on Restaurant Taxes in Indramayu Regency - Dian Hartika; Ida Rosnidah; Moh. Taufik Hidayat (ijd-demos, 2022)
AbstractThis study aims to analyze the implementation of monitoring local taxes based on information systems on restaurant taxes in Indramayu Regency as one of the potentials to increase local tax revenues through restaurant taxes conducted by the Regional Finance Agency of Indramayu Regency. This study uses a qualitative approach, with the type of descriptive research. The strategy for implementing the policy of installing transaction recording devices as monitoring local taxes on restaurant taxes in Indramayu Regency can be said to be appropriate and optimal in its implementation. The inhibiting factor for the strategy of implementing the policy of installing transaction recording devices as monitoring local taxes on restaurant taxes in Indramayu Regency is the limitations of transaction recording tools so that at first taxpayers objected to installing transaction recording devices. In addition, other obstacles exist on the part of taxpayers such as power failures so that reporting when transactions do not enter the BKD server, server errors resulting in double entry causing nominal differences, as well as LAN connections at the Regional Finance Agency. The supporting factor for the strategy of implementing the policy of installing transaction recording devices as monitoring local taxes on restaurant taxes in Indramayu Regency lies in the mutual support between the leadership and all staff related to the implementation of monitoring transaction recording devices. While externally, it can be seen from the good cash flow turnover and the large number of visitors, thus supporting good tax revenue and the holding of tax monitoring with transaction recording tools, so that the tax monitoring system in Indramayu Regency is increasing every year.Keywords: Policy Implementation, Local Tax, Transaction Record Tool. AbstrakPenelitian ini bertujuan untuk menganalisis pelaksanaan monitoring pajak daerah berbasis sistem informasi pajak restoran di Kabupaten Indramayu sebagai salah satu potensi untuk meningkatkan penerimaan pajak daerah melalui pajak restoran yang dilakukan oleh Badan Keuangan Daerah Kabupaten Indramayu. Penelitian ini menggunakan pendekatan kualitatif, dengan jenis penelitian deskriptif. Strategi penerapan kebijakan pemasangan alat pencatatan transaksi sebagai monitoring pajak daerah atas pajak restoran di Kabupaten Indramayu dapat dikatakan tepat dan optimal dalam pelaksanaannya. Faktor penghambat strategi pelaksanaan kebijakan pemasangan alat pencatatan transaksi sebagai monitoring pajak daerah atas pajak restoran di Kabupaten Indramayu adalah keterbatasan alat pencatatan transaksi sehingga pada awalnya wajib pajak keberatan dengan pemasangan alat pencatatan transaksi. Selain itu, kendala lain yang ada di pihak Wajib Pajak seperti listrik padam sehingga pelaporan saat transaksi tidak masuk ke server BKD, server error sehingga terjadi double entry yang menyebabkan perbedaan nominal, serta koneksi LAN di Badan Keuangan Daerah. Faktor pendukung strategi pelaksanaan kebijakan pemasangan alat pencatatan transaksi sebagai pemantau pajak daerah atas pajak restoran di Kabupaten Indramayu terletak pada saling mendukung antara pimpinan dengan seluruh jajaran terkait pelaksanaan pemantauan alat pencatatan transaksi. Sedangkan secara eksternal dapat dilihat dari perputaran arus kas yang baik dan jumlah pengunjung yang banyak, sehingga mendukung penerimaan pajak yang baik dan diadakannya pengawasan pajak dengan alat pencatatan transaksi, sehingga sistem pengawasan pajak di Kabupaten Indramayu semakin meningkat setiap tahunnya.Kata kunci: Implementasi Kebijakan, Pajak Daerah, Alat Pencatatan Transaksi